IMPAK IKLIM ORGANISASI TERHADAP `BURNOUT' DI KALANGAN GURU PENDIDIKAN JASMANI DAN KESIHATAN (PJK) - Haraman, Mohd. Hassan (Universiti Malaysia Sarawak, (UNIMAS), 2004)
The conduct of this research is to indicate early connection between 'burnout ' and organizational climate among teachers of PHE. The research was conducted in several primary and secondary schools grade 'A', 'B', and 'C' in Kuching and Kota Samarahan, Sarawak. The research aims to further investigate the impact of organizational climate in schools and its level of relationship with 'burnout'. Five dimensions were used to measure the level of organizational climate which consist of aspects of psychological, bureaucratic, structural and social. As for 'burnout' inventory three factors were considered of'physical, mental and emotional. A many as 110 respondents were involved for this research. The Statistical Package for Social Science (SPSS) Window Release Version 11.5 application was used for data analysis. Result of analysis indicates a low 'burnout' level among PHE teachers (M=2.24). T-test analysis shows that there exists a significant relationship for 'burnout' among PHE teachers with marital status (T=-0.034, K<0.05). Findings of research indicate a significant relationship among each dimensions of organizational climate with PHE teachers 'burnout'. Double Stepwise Regression analysis carried out, indicates that structural dimension as the most dominant prediction variable for 'burnout' indication among PHE teachers (B=0.280). Steps were taken to improve conducive organizational climate prevent to a 'burnout' and related proposal for new research is also highlighted.